(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
Rice is the staple food for 3.5 billion people worldwide, and soil salinity poses a major threat to its production in countries like Bangladesh. This study, conducted at the Plant Breeding Division of BINA, aimed to identify salinity-tolerant rice genotypes. Fourteen landraces, three advanced lines, with three check varieties were hydroponically screened at the seedling stage under EC 8, 12, and 14 dS m⁻¹ following IRRI standard protocols. After 21 days of salinization, six genotypes were identified as tolerant, five as moderately tolerant, and the remainder as susceptible at EC 14 dS m⁻¹ based on SES score. ANOVA revealed significant differences among genotypes for shoot length, root length, shoot and root fresh and dry weights, and standard evaluation score (SES), with most traits significant at 0.1% probability. Path coefficient analysis indicated that root fresh weight, root dry weight, and shoot length had direct positive effects on SES at the genotypic level, while shoot fresh weight and shoot length were positively influential at the phenotypic level. All traits showed higher phenotypic than genotypic coefficients of variation, indicating environmental influence, and heritability ranged from 80.84% to 99.10%, highest for shoot length. Molecular confirmation of Saltol QTL with three SSR markers (RM7075, RM1287, RM10772) detected an average of 10 alleles per locus, with PIC values from 0.700 to 0.914. Combining morphological and molecular data, Khasrael, Kajolsael, Khusi, Patnai, Rajasael, and Kasfulbalam were identified as salt-tolerant, providing valuable material for breeding programs. Bangladesh J. Nuclear Agric, 39(2): 17-34, 2025